Antiangiogenic therapy in oncology: current status and future directions. Issue 10043 (30th July 2016) - Jayson, Gordon C; Kerbel, Robert; Ellis, Lee M; Harris, Adrian L
Summary: Angiogenesis, the formation of new blood vessels from pre-existing vessels, has been validated as a target in several tumour types through randomised trials, incorporating vascular endothelial growth factor (VEGF) pathway inhibitors into the therapeutic armoury. Although some tumours such as renal cell carcinoma, ovarian and cervical cancers, and pancreatic neuroendocrine tumours are sensitive to these drugs, others such as prostate cancer, pancreatic adenocarcinoma, and melanoma are resistant. Even when drugs have yielded significant results, improvements in progression-free survival, and, in some cases, overall survival, are modest. Thus, a crucial issue in development of these drugs is the search for predictive biomarkers—tests that predict which patients will, and will not, benefit before initiation of therapy. Development of biomarkers is important because of the need to balance efficacy, toxicity, and cost. Novel combinations of these drugs with other antiangiogenics or other classes of drugs are being developed, and the appreciation that these drugs have immunomodulatory and other modes of action will lead to combination regimens that capitalise on these newly understood mechanisms.